Ethnobotanical survey on plants used in the treatment of candidiasis in traditional markets of southern Benin - Brice Armand Fanou; Jean Robert Klotoe; Lauris Fah; Victorien Dougnon; Charles Hornel Koudokpon; Ghislaine Toko; Frédéric Loko (BMC, 2020)
Abstract Background Candidiasis, an opportunistic cosmopolitan disease is nowadays like bacterial infections which is a real public health problem. In view of the emergence of Candida strains resistant to existing antifungal agents, alternative solutions should be considered. This is the purpose of this ethnobotanical survey, which aims to identify the medicinal plant species traditionally used to treat candidiasis in traditional markets of southern Benin. Methods The study was performed from October 2015 to January 2018 in the traditional markets of Southern-Benin. Data were collected by two complementary methods: triplet purchase of medicinal recipes (ATRM) from herbalists markets and semi-structured interview (ISS) from traditional healers. Results A total of 109 species of medicinal plants belonging to 44 families have been listed and identified. The most frequently cited species were Pteleopsis suberosa Engl. & Diels, Lantana camara L., Cyanthillium cinereum (L.) H. Rob, Ocimum gratissimum L. and Lippia multiflora Moldenke with respectively 43.84, 39.73 and 34.25% citation frequencies for the last three species respectively. Leguminosae (20.18%), Euphorbiaceae (5.50%) and Apocynaceae (5.50%) were the most represented botanical families. Leafy stems were more used than other plant organs. The decoction and the oral route were the most appropriate methods of preparation and administration reported by traditional healers. Conclusion Benin's plant cover is made up of a wide variety of medicinal plant species used in the traditionnal treatment of candidiasis and which may constitute new sources of medicines to be developed.